2022
DOI: 10.48550/arxiv.2201.00131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct determination of entanglement monotones for arbitrary dimensional bipartite states using statistical correlators and one set of complementary measurements

Abstract: Higher dimensional quantum systems (qudits) present a potentially more efficient means, compared to qubits, for implementing various information theoretic tasks. One of the ubiquitous resources in such explorations is entanglement. Entanglement Monotones (EMs) are of key importance, particularly for assessing the efficacy of a given entangled state as a resource for information theoretic tasks. Till date, investigations towards determination of EMs have focused on providing their tighter lower bounds. There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…For a pure bipartite qutrit state, the validity of Eq. ( 35) has recently been demonstrated experimentally in [27].…”
Section: Pearson Correlation Coefficient Based Boundsmentioning
confidence: 93%
See 1 more Smart Citation
“…For a pure bipartite qutrit state, the validity of Eq. ( 35) has recently been demonstrated experimentally in [27].…”
Section: Pearson Correlation Coefficient Based Boundsmentioning
confidence: 93%
“…A key shift in focus from the above-mentioned line of studies has been made in the latest study reported in a separate paper [27], where by harnessing the maximum complementarity of one or two pairs of mutually unbiased measurement bases, the EMs like Negativity (N) and Entanglement of Formation (EOF) of any bipartite pure state have been analytically related to the observable statistical correlators like MP, MI and PCC for any dimension. Moreover, this general scheme has been applied for the experimental determination of N and EOF of a prepared two qutrit pure photonic state, using the analytically derived relationships.…”
Section: Introductionmentioning
confidence: 99%